Answer:
x/3-10=8
x/3=18
x=48
Step-by-step explanation:
24 and 25 divide will give you the final answer
The solution to the inequality expression is x ≥ 30
<h3>How to solve the
inequality expression?</h3>
The inequality expression is given as:
8x - 3(2x - 4) ≤ 3(x - 6)
Open the brackets in the above inequality expression
8x - 6x + 12 ≤ 3x - 18
Collect the like terms in the above inequality expression
8x - 6x - 3x ≤ -12 - 18
Evaluate the like terms in the above inequality expression
-x ≤ -30
Divide both sides of the above inequality expression by -1
x ≥ 30
Hence, the solution to the inequality expression is x ≥ 30
Read more about inequality expression at
brainly.com/question/24372553
#SPJ1
Answer:
69
Step-by-step explanation:
What is the graph?
2x + 5y = 2
-3x - y =-3
-3x - y = -3
y = 3x - 3
substitute y = 3x - 3 into the first equation.
2x + 5y = 2
2x + 5(3x - 3) = 2
2x + 15x - 15 = 2
17x - 15 = 2
solve for x in 17x - 15 = 2
17x - 15 = 2
17x = 2 + 15
17x = 17
x = 1
substitute x = 1 into y = 3x - 3
y = 3x - 3
y = 3(1) - 3
y = 3 - 3
y = 0
(1, 0) << the answer
hope this helped, God bless!